(untitled) (Journal of Engineering, 2006)
This Paper aims an identifying the tests of mosaic tiles and incorporated it into management systems, to assist, authors of system that has mosaic tiles is technically accepted (accept lie). This paper presents the important tests taken from the British specifications adding to it other tests which might be necessary to complement the test of the tile that has been technically accepted. The results that were depended on were numbers which might be nearer to reality respecting the used tiles whose results were taken from: 1- The tests that were performed in the lab of testing constructional material/College of Engineering/ University of Baghdad. 2- The test that were performed in the National Center of Constructional Labs. 3- Depending on previous Researches in this field. According to the information, the results of the test and the number of the used tiles in Iraq were established. Then the theoretical information of the research and the lab’s result were taken and a management system was made for an information basis of one of the expert systems. Through inputting data by the user of the program to this system, the range of fitness of using the tile could be known.